Research Review of the Knowledge Graph and its Application in Power System Dispatching and Operation - Chen, Junbin; Lu, Guanhua; Pan, Zhenning; Yu, Tao; Ding, Maosheng; Yang, Huibiao (Frontiers in Energy Research, 2022)
With the construction of new power system and the proposal of double carbon goal, the optimization of power system dispatching operation is becoming more and more complex. Relying on traditional pure manual dispatching is difficult to meet the dispatching needs. The emerging knowledge graph technology in the field of artificial intelligence technology is one of the effective methods to solve this problem. Knowledge graph is a structured semantic knowledge base that represents entities and their relationships in the objective world in the form of graph. It is composed of triples such as "entity relationship entity". Because the topological structure of power system itself is consistent with the relational structure of graph theory, expressing the hidden knowledge in power system dispatching operation in the form of knowledge graph has become the focus of research at home and abroad. This paper summarizes the development of knowledge graph technology from the aspects of knowledge extraction, knowledge representation learning, knowledge mining, knowledge reasoning, knowledge fusion and the application of knowledge graph, and from the aspects of load balance, vertical risk control, operation mode analysis, auxiliary optimization decision-making This paper introduces some scenario applications and prospects of knowledge atlas in power system dispatching operation from the perspective of super parameter regulation.